Complications and survival analyses of hip arthroscopies performed in the national health service in England: a review of 6,395 cases - Malviya, Ajay; Raza, Ali; Jameson, Simon; James, Philip; Reed, Mike R; Partington, Paul F (Arthroscopy, 2015)
Our study aimed to identify the complications of hip arthroscopies with particular emphasis on the 30-day readmission rate; 90-day deep vein thrombosis (DVT) and pulmonary embolism (PE) rate and mortality rate; revision hip arthroscopy rate; and in particular, survivorship with conversion to total hip replacement (THR) as the endpoint. The records of patients undergoing hip arthroscopy were extracted from the administrative hospital admissions database covering all admissions to the National Health Service hospitals in England using ICD-10 (International Statistical Classification of Diseases and Related Health Problems, 10th Revision) and OPCS-4 (Office of Population Censuses and Surveys Classification of Surgical Operations and Procedures, fourth revision) codes. A total of 6,395 hip arthroscopies were included in the study period. The 30-day readmission rate was 0.5%; both the 90-day DVT rate and PE rate were 0.08%; and the 90-day mortality rate was 0.02%. THR was performed in 680 patients (10.6%) at a mean of 1.4 years after the index operation, and 286 patients (4.5%) underwent revision hip arthroscopy at a mean of 1.7 years. Kaplan-Meier survival analysis showed an 8-year survival rate of 82.6% (95% confidence interval [CI], 80.9% to 84.2%), whereas Cox proportional hazard analysis adjusting for age, gender, and Charlson comorbidity score showed an 8-year survival rate of 86%. Female patients had a 1.68 times (95% CI, 1.41 to 2.01) higher risk of conversion to THR than male patients, and patients aged 50 years or older had a 4.65 (95% CI, 3.93 to 5.49) times higher risk of requiring hip replacement than patients younger than 50 years. In this large series of 6,395 hip arthroscopies looking at the national data from the English National Health Service, our null hypothesis has been supported, and we have determined that the rate of short-term complications, in particular the risk of DVT and PE after this operation, is low. Higher age and female gender are significant predictors of conversion to THR, with Cox proportional hazard analyses showing a survivorship rate of 86% at 8 years after adjustment for confounding variables. Level IV, therapeutic case series.